Self-Assembly and Drug Release Capacities of Organogels via Some Amide Compounds with Aromatic Substituent Headgroups - Zhang, Lexin (Materials (Basel), 2016)
In this work, some amide compounds with different aromatic substituent headgroups were synthesized and their gelation self-assembly behaviors in 22 solvents were characterized as new gelators. The obtained results indicated that the size of aromatic substituent headgroups in molecular skeletons in gelators showed crucial effect in the gel formation and self-assembly behavior of all compounds in the solvents used. Larger aromatic headgroups in molecular structures in the synthesized gelator molecules are helpful to form various gel nanostructures. Morphological investigations showed that the gelator molecules can self-assembly and stack into various organized aggregates with solvent change, such as wrinkle, belt, rod, and lamella-like structures. Spectral characterizations suggested that there existed various weak interactions including π-π stacking, hydrogen bonding, and hydrophobic forces due to aromatic substituent headgroups and alkyl substituent chains in molecular structures. In addition, the drug release capacities experiments demonstrated that the drug release rate in present obtained gels can be tuned by adjusting the concentrations of dye. The present work would open up enormous insight to design and investigate new kind of soft materials with designed molecular structures and tunable drug release performance.